Green Mobility Implementation Strategy: A SWOT Analysis Approach - Ahyani, Ahyani; Sarjana, Sri; Ma'arif, Guntoro Zain; Hardianto, Dani; Nomin, Nomin (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2024)
Green mobility is one of the main solutions to reduce the environmental impact of transportation, as well as to support sustainable urban development. This study aims to identify strategies for implementing green mobility in urban areas using the SWOT (Strengths, Weaknesses, Opportunities, Threats) and STP (Segmentation, Targeting, Positioning) analysis approaches. This study uses a qualitative method based on literature studies that examine various sources related to policies, infrastructure, and green mobility practices in various cities. The results of the SWOT analysis show that the main strength of green mobility implementation lies in green mobility being an environmentally friendly transportation with low operational costs and can reduce congestion, although there are weaknesses in terms of inadequate infrastructure and resistance to behavioral change. Opportunities that can be utilized include support from government policies and global trends towards smart cities and increased investment in the environmentally friendly transportation sector, while threats faced by resistance from the conventional vehicle industry include high dependence on private motor vehicles. In the STP analysis, market segmentation is carried out based on geographic, demographic, and psychographic characteristics, targeting urban workers who are more open to environmentally friendly transportation solutions. Green mobility is positioned as an efficient, cost-effective, and environmentally friendly transportation option. Based on the analysis results, it is suggested that transportation policies that support green mobility focus on developing better infrastructure, educational campaigns, and policy support from the government. Thus, the implementation strategy obtained is green mobility education to the community, development of supporting infrastructure, provision of incentives and subsidies, and government policies that support the implementation of green mobility.